TINGGALAN ARKEOLOGI DI KAMPUNG ARAB - Masyhudi Masyhudi (Balai Arkeologi Yogyakarta, 2010)
The Arabs are anation that has long been known to be succeeded in influencing other nations. It is, among others, proven by the wide-spread of Islam through a variety of ways, i.e. politic, tasawwuf, trade, or marriage, although later trade is considered as the most dominant step that allegedly committed by Arabs.Geographically, Semarang and Surakarta are two cities located differently, Semarang is located on the north coast of Java, while Surakarta is located in the mainland. Both have a long history in the development of Islam in Java. In Semarang as well as Surakarta, could be found the Arabs community. This paper tries to discuss from where and when the Arabs came to both cities as well as their first purpose at their arrival.